VERA monitoring of the radio jet 3C 84 in the period of 2007–2013: Detection of non-linear motion. (20th July 2018) - Hiura, Koichiro; Nagai, Hiroshi; Kino, Motoki; Niinuma, Kotaro; Sorai, Kazuo; Chida, Hikaru; Akiyama, Kazunori; D'Ammando, Filippo; Giovannini, Gabriele; Giroletti, Marcello; Hada, Kazuhiro; Honma, Mareki; et al.
Abstract: We present a kinematic study of the sub-parsec-scale radio jet of the radio galaxy 3C 84/NGC 1275 with the VLBI Exploration of Radio Astrometry (VERA) array at 22 GHz for 80 epochs from 2007 October to 2013 December. The averaged radial velocity of the bright component "C3" with reference to the radio core is found to be 0.27 ± 0.02 c between 2007 October and 2013 December. This constant velocity of C3 is naturally explained by the advancing motion of the head of the mini-radio lobe. We also find a non-linear component in the motion of C3 with respect to the radio core. We briefly discuss possible origins of this non-linear motion.